Prognostic value of integrated morphofunctional imaging methods in inoperable intrahepatic cholangiocarcinoma - Nanni, Cristina; Mosconi, Cristina; Dragonetti, Valentino; Barakat, Massimo; Fraccascia, Nicola; Cocozza, Maria Adriana; Brocchi, Stefano; Palloni, Andrea; Paccapelo, Alexandro; Brandi, Giovanni; Fanti, Stefano (Frontiers in Medicine, 2023)
Intrahepatic cholangiocarcinoma(iCCA) is a disease characterized by rarity, heterogeneity and high mortality, where surgical resection is often not possible.Nowadays, thanks to the recent introduction of new therapeutic options such as Trans-Arterial Radioembolization (TARE), it is increasingly important to define the role of morphofunctional imaging methods for prognostic stratification of patients affected by iCCA. The aim of the study was to verify the prognostic value of morphofunctional imaging methods at baseline in patients with inoperable iCCA. 45 patients with iCCA were sent to our centre between January 2016 and March 2021 for being evaluated to be treated with TARE.All of them underwent both [18F]-FDG-PET/CT and contrast-enhanced CT (ceCT) in a single procedure and were included in our study. The inclusion criteria were: a diagnosis of inoperable iCCA; both [18F]-FDG-PET/CT and ceCT scans; washout from therapy for at least 2 months before baseline [18F]-FDG-PET/CT and ceCT scans.Both clinical, laboratory data and baseline imaging data (ceCT and [18F]-FDG-PET/CT) were collected.In particular, regarding clinical and laboratory data: overall survival (OS), gender, age, prior therapies, liver function indices and tumor markers. Regarding ceCT: TNM staging, lesion diameter, volume, vascularization, and presence of intravascular necrosis. Regarding [18F]-FDG-PET/CT: TNM staging, Standard-Uptake-Value max (SUVmax), Metabolic-Tumor-Volume (MTV) and To-tal-Lesion-Glycolysis (TLG=MTV*lesions SUVmean). Philips-Vue-PACS software was used, setting hepatic SUVmean as TLG threshold. A statistically significant correlation was found between some examined parameters at morphofunctional investigations at baseline and OS. [18F]-FDG-PET/CT parameters statistically correlated with OS were stage of disease greater than M0 (p=0.037), major lesion SUVmax (p=0.010), MTV (p=<0.001) and TLG (p<0.001). Other parameters at ceCT correlated with OS were stage of disease greater than T2 (p=0.038), maximum lesion diameter (p=0.07), volume of the major lesion (p=0.016) and total volume of lesions(p=0. 009). Biochemical parameters correlated with OS were gamma glutamyl transferase (GGT, p=0.014), alkaline phosphatase (ALP, p=0.019), carcinoembryonic antigen (CEA, p=0.004) and carbohydrate antigen 19-9 (CA 19-9, p<0.001). From the parameters estimated by the multivariate model we derived a 4-variables score for OS combining nodal involvement and SUVmax at [18F]-FDG-PET/CT, GGT,CA 19-9 levels. Considering our data, integrated pre-therapy imaging is critical for the prognostic stratification of patients with iCCA.